2021
DOI: 10.48550/arxiv.2105.07297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalized Turán results for intersecting cliques

Abstract: For fixed graphs F and H, the generalized Turán problem asks for the maximum number ex(n, H, F ) of copies of H that an n-vertex F -free graph can have. In this paper, we focus on cases with F being B r,s , the graph consisting of two cliques of size s sharing r common vertices. We determine ex(n, K t , B r,0 ), ex(n, K a,b , B 3,1 ) for any values of a, b, r, t if n is large enough and ex(n, K r+t , B r,s ) if 2s + t + 1 < r and n is large enough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Gerbner [8] extended this to any K a,a with a > 2 in place of C 4 . Let K + a,b denote the graph we obtain from K a,b by adding an edge to the part of size a. Gerbner and Patkós [12] showed that ex(n, K a,b , F 2 ) = N (H, K + m,n−m ) for some m. Perhaps the most natural questions concerning generalized Turán problems for double stars are counting cliques or counting double stars when a double star is forbidden. We resolve both questions by the following results.…”
Section: Introductionmentioning
confidence: 99%
“…Gerbner [8] extended this to any K a,a with a > 2 in place of C 4 . Let K + a,b denote the graph we obtain from K a,b by adding an edge to the part of size a. Gerbner and Patkós [12] showed that ex(n, K a,b , F 2 ) = N (H, K + m,n−m ) for some m. Perhaps the most natural questions concerning generalized Turán problems for double stars are counting cliques or counting double stars when a double star is forbidden. We resolve both questions by the following results.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [19] determined ex(n, K s , tK 2 ) for every n, s, t. Liu and Wang [13] determined ex(n, K r , 2K r ) for sufficiently large n, while Gerbner and Patkós [9] determined ex(n, K s , 2K r ) for sufficiently large n. Yuan and Yang [18] obtained a threshold on n, and determined ex(n, K 3 , 2K 3 ) for every n. A result of Gerbner [7] implies an exact result on ex(n, K s , tK r ) in the case s < r for sufficiently large. We do not state these results, as our results generalize each of them, in the case n is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…A new proof of ex(n, K r , 2K r ) can be found in [21] by Yuan and Yang. Gerbner and Patkós [9] determined ex(n, K s , 2K r ) for all s ≥ r ≥ 3 and n sufficiently large. In this paper, we determine the value of ex(n, K r , (k + 1)K r ) for all r ≥ 2, k ≥ 1 and n sufficiently large.…”
Section: Introductionmentioning
confidence: 99%